2020
DOI: 10.1136/jitc-2020-000734
|View full text |Cite
|
Sign up to set email alerts
|

The Society for Immunotherapy of Cancer consensus statement on immunotherapy for the treatment of multiple myeloma

Abstract: Outcomes in multiple myeloma (MM) have improved dramatically in the last two decades with the advent of novel therapies including immunomodulatory agents (IMiDs), proteasome inhibitors and monoclonal antibodies. In recent years, immunotherapy for the treatment of MM has advanced rapidly, with the approval of new targeted agents and monoclonal antibodies directed against myeloma cell-surface antigens, as well as maturing data from late stage trials of chimeric antigen receptor CAR T cells. Therapies that engage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 206 publications
0
24
0
Order By: Relevance
“…Although most patients with multiple myeloma respond well to initial chemotherapy combinations, the disease almost always relapses and eventually becomes resistant to therapy. BsAbs have shown particular efficacy in B cell malignancies, with some of the most promising clinical trials in development for multiple myeloma with agents targeting the antigen BCMA, encoded by the TNFRSF17 gene (2). There are multiple BCMA/ CD3 BsAbs or BiTEs in phase I clinical trials in heavily pretreated patients with multiple myeloma.…”
mentioning
confidence: 99%
“…Although most patients with multiple myeloma respond well to initial chemotherapy combinations, the disease almost always relapses and eventually becomes resistant to therapy. BsAbs have shown particular efficacy in B cell malignancies, with some of the most promising clinical trials in development for multiple myeloma with agents targeting the antigen BCMA, encoded by the TNFRSF17 gene (2). There are multiple BCMA/ CD3 BsAbs or BiTEs in phase I clinical trials in heavily pretreated patients with multiple myeloma.…”
mentioning
confidence: 99%
“…Since there is no specific treatment for patients with SMM, high-risk patients are treated with agents approved for symptomatic MM. In MM, several immunotherapies have been approved against CD38 ( 31 ), signaling lymphocytic activation molecule F7 (SLAMF7) and B cell maturation antigen (BCMA) ( 32 , 33 ). In this study, we found several inhibitory immune checkpoints (TIGIT, CD96, BTLA, LAG3, KLRC1) upregulated in high-risk SMM patients, some of them being currently tested in clinical trials for patients with relapsed refractory MM, such as dual blockade of TIGIT and LAG-3 (NCT04150965).…”
Section: Discussionmentioning
confidence: 99%
“…A small case series of nine patients showed a promising response rate in patients treated with an isatuximab-based regimen after prior daratumumab therapy [ 128 ]. There is currently no consensus recommendation about the retreatment with daratumumab [ 129 ]. Sequencing of antibodies is another challenging issue.…”
Section: Conclusion—beyond the Moab Therapymentioning
confidence: 99%